Illegal intra-corporeal packets: can dual energy CT be used for the evaluation of cocaine concentration? A cross sectional study. Issue 1 (December 2016) - Platon, Alexandra; Becker, Minerva; Becker, Christoph; Lock, Eric; Wolff, Hans; Perneger, Thomas; Poletti, Pierre-Alexandre
Abstract Background The recent implementation of the dual energy technology on CT-scanners has opened new perspectives in tissue and material characterization. This study aims to evaluate whether dual energy CT can be used to assess the concentration of cocaine of intra-intestinal illegal packets. Methods The study was approved by the institutional review board of our institution (CER 13_027_R). From November 2010 to May 2013, all consecutive conveyors in whom a low-dose abdominal CT (LDCT) revealed the presence of illegal intra-corporeal drug packets underwent a dual energy CT series (gemstone spectral imaging) targeted on one container. The mean radiological density (HU) of these packets was measured on the LDCT series, and on the monochromatic dual energy series, at 40 and 140 keV. The difference between the HU at 40 and 140 keV was reported as ∆HU. The effective atomic number Z(eff) was also measured on the monochromatic series. A chemical analysis was performed after expulsion to select cocaine containing packets, and to determine their cocaine concentrations. A correlation analysis was performed between HU, ∆HU and Z(eff), with regard to the percentage of cocaine. Results Fifty-four cocaine conveyors were included. The mean cocaine content of the packets was 36.8 % (range 11.2–80, SD 15.4), the mean radiologic density 105 HU, the mean Z(eff) 8.7 and the mean ∆HU 163. The cocaine content was correlated with the ∆HU (0.57, p < 0.001), with the Z(eff) (r = 0.56, p < 0.001) but not with radiologic density (r = 0.25, p = 0.064). ∆HU >200 was 0.9 (9 of 10) sensitive and 0.82 (36 of 44) specific to predict a cocaine concentration higher than 50 %. Conclusion Measuring ∆HU or Z(eff) on dual energy monochromatic CT series can be used to detect ingested packets with cocaine concentration >50 %.